Analisis Strategi Pemasaran dalam Meningkatkan Penjualan Batik Tulis di Toko Asofa - Lailatul Zannah; Maslahah Maslahah; Santika Dewi; Sri Yuedah; Dini Selasi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze the marketing strategies used at the Asofa Batik Shop to increase batik sales. Researchers use a descriptive qualitative approach, which describes phenomena or situations in depth and detail using qualitative data such as text, images, audio and video. The results of this research are that, the marketing strategy he used after being allocated to branches or sorum (Asofa Written Batik Shop), apparently the Asofa batik shop owner had collaborated with DT Peduli Cirebon (digital marketing training), after which the Asofa batik owner finally developed business through digital marketing platforms such as Facebook, Shoppe, Lazada, Tokopedia, which can be purchased offline or online. One of the challenges in implementing a marketing strategy is facing intense competition from other batik producers at local and national levels. Mr. H. Bachroni is committed to prioritizing Indonesian cultural heritage, one of which is batik by providing friendly service and offering affordable batik product prices. So that buyers can make Asofa Cirebon batik an attractive place to shop.